2020
DOI: 10.1177/2516598420939740
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on flexible pad polishing for nano-finishing of freeform optics mold

Abstract: The need for freeform surfaces are widely recognized in the optical, aerospace, biomedical, and automotive industries. However, the fabrication of freeform surfaces is very difficult and expensive because of the involvement of advanced, multi-axis, dedicated machining processes. In many applications, the machining surface needs further polishing to reduce the surface roughness. The main aim of this work is to investigate the flexible pad polishing process for the finishing of the freeform surface. To achieve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…CNC controlled tool movement [157] and well-designed fixtures hold immense potential for precise and efficient MAF of complex, free-form surfaces. CNC program ensures the consistent brush movement for uniform finishing across free-form low-depth geometries [158]. Lin et al (2007) demonstrated achieving surface roughness up to 0.1 μm on free-form surface of stainless SUS 304 workpiece using CNCcontrolled MAF [36].…”
Section: Challenges In Advancing the Maf Process For Future Workmentioning
confidence: 99%
“…CNC controlled tool movement [157] and well-designed fixtures hold immense potential for precise and efficient MAF of complex, free-form surfaces. CNC program ensures the consistent brush movement for uniform finishing across free-form low-depth geometries [158]. Lin et al (2007) demonstrated achieving surface roughness up to 0.1 μm on free-form surface of stainless SUS 304 workpiece using CNCcontrolled MAF [36].…”
Section: Challenges In Advancing the Maf Process For Future Workmentioning
confidence: 99%
“…[3][4][5][6][7] CMP is primarily used for silicon, but it can also potentially be used for other materials including sapphire [8][9][10][11] but only on planar surfaces. Mishra et al 12 have investigated the flexible pad polishing process for the finishing of the freeform surface. They have developed a flexible pad polishing setup that can be integrated with a computer numerical control (CNC) machine, which is capable of polishing the conventional rotationally symmetric surfaces as well as freeform surfaces.…”
Section: Introductionmentioning
confidence: 99%